Respuesta :

A negative number raised to an even power will produce a positive result.

... (-1)² = 1

Answer : The required expression is, [tex](-1)^{2n}[/tex]

Step-by-step explanation :

The expression with (-1) as its base that will produce a positive product is written as:

[tex](-1)^{2n}[/tex]

where,

'n' is a natural number

For example :

When we take the value of n = 1, then we get [tex](-1)^{2n}=(-1)^{2\times 1}=1[/tex] which is a positive product.

When we take the value of n = 2, then we get [tex](-1)^{2n}=(-1)^{2\times 2}=1[/tex] which is a positive product.

When we take the value of n = 3, then we get [tex](-1)^{2n}=(-1)^{2\times 3}=1[/tex] which is a positive product.

That means when we take any natural number in this expression, then it will give a positive product.

Hence, the required expression is, [tex](-1)^{2n}[/tex]